Ethics of transitions : what world do we want to live in together? - Dratwa, Jim (Interdisciplinarity, science and humanities series. Innovation and responsibility set, 2022)
This book covers all forms of ethical assessment of research and innovation at the European Commission, including the implications of the concept of RRI which has emerged as a new framework to be used by the European Commission, and indeed including the newer concepts of Open Innovation and Open Science which are designed to subsume and reconfigure RRI. The book can be used as a 'how to' guide to understand and navigate the ethical and societal demands in developing European research projects; it also pushes the reflection and reflexivity further, bringing provoking new (and also some very old) perspectives to bear on ardent debates in studies of expertise, ethics and policy making.